2020
DOI: 10.22302/iccri.jur.pelitaperkebunan.v36i2.437
|View full text |Cite
|
Sign up to set email alerts
|

Grouping Tolerant Level of Cocoa Genotypes Against Pod Rot Disease in Malaysia

Abstract: Cocoa pod rot disease (CPRD), caused by Phytophthora palmivora, is the main disease that caused major losses in Malaysia. It is important for screening the cocoa genotypes available in Malaysia for their tolerance level against the CPRD. This paper has an objective to select the potential genotypes tolerant to P. palmivora by grouping the cocoa genotypes available in Malaysia based on four tolerant levels such as tolerant, moderately tolerant, moderately susceptible and susceptible. The experiment was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Genetic variance contributes greatly to a classification method that can objectively identify the degree of similarity and differences in genotypes tested in breeding programs. The high contribution of genetics in this study is indicated by the high heritability value of each character evaluated, indicating that the assessment also involves a genetic contribution in the grouping of resistance status (Chang et al, 2020;De Oliveira et al, 2016;Moral et al, 2021). The resistance groups formed can represent the resistance status of the genotypes tested.…”
Section: Variance and Heritability Of Resistance Character Of Shallotmentioning
confidence: 87%
See 1 more Smart Citation
“…Genetic variance contributes greatly to a classification method that can objectively identify the degree of similarity and differences in genotypes tested in breeding programs. The high contribution of genetics in this study is indicated by the high heritability value of each character evaluated, indicating that the assessment also involves a genetic contribution in the grouping of resistance status (Chang et al, 2020;De Oliveira et al, 2016;Moral et al, 2021). The resistance groups formed can represent the resistance status of the genotypes tested.…”
Section: Variance and Heritability Of Resistance Character Of Shallotmentioning
confidence: 87%
“…The second group (green) consisted of Batu Ijo, Maja Cipanas, Rubaru, and Agrihorti I. The K-means method to classify varieties based on disease resistance characteristics has been widely used, such as banana plants, for grouping resistance to fusarium wilt (Ribeiro et al, 2017), cacao (Chang et al, 2020), and almond (Moral et al, 2021). K-means was used to group resistance status because it can determine different resistance groups based on the resistance characteristics of the tested genotypes (Lisiecki et al, 2022).…”
Section: Determination Of Susceptibility Groupmentioning
confidence: 99%